Analysis The Dept of visual Aesthetic Value furniture - Gebby Miranda; Salsa Nafsika; Nala Nandana (Universitas Pendidikan Indonesia, 2022)
Aesthetics is a philosophical science that talks about everything that is called beautiful, the beauty contained in a work of art which is a form of creativity of an artist. Our goal is to analyze the depth of the aesthetic value of the good day coffee advertisement, seeing the lack of public knowledge about art in advertisements, they only see that the advertisement is beautiful without seeing the depth of aesthetic value and form in the work. It is said that the existence of art (advertising) is only controlled by art academics, curators, connoisseurs and art observers. The method is by looking at a work and then analyzing it and connecting it with aesthetic values and forms from various sources, then, it is processed using interpretive and descriptive methods so that readers can understand or re-explain properly and correctly. In analyzing this advertisement, the focus of the study is, what is the general description and the depth of aesthetic value and form in the work. The results of the study show that, not only visual products and music, but also property is needed so that the audience can enjoy it.